2013
DOI: 10.1124/jpet.113.207233
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTION: Role of Angiotensin-(1–7) in Gastroprotection against Stress-Induced Ulcerogenesis. The Involvement of Mas Receptor, Nitric Oxide, Prostaglandins, and Sensory Neuropeptides

Abstract: Angiotensin-(1-7) [Ang-(1-7)] is a major vasoactive metabolite of angiotensin I (Ang I), both being important components of the renin-angiotensin system (RAS). Ang-(1-7) acting via Mas receptor was documented in kidneys, heart, brain, and gastrointestinal (GI)-tract. We studied the gastroprotective activity of exogenous Ang-(1-7) in rats exposed to water immersion and restraint stress (WRS) without or with A-779, the agonist of Ang-(1-7) receptor, as well as the inhibition of nitricoxide (NO) synthase, the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…WRS is often used as a stress treatment to induce stress response syndromes in animals (8)(9)(10)(11)(12)(13)24). In the present study, WRS successfully reduced the BMD via a high bone turnover rate; WRS induced an increase in bone resorption and formation.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…WRS is often used as a stress treatment to induce stress response syndromes in animals (8)(9)(10)(11)(12)(13)24). In the present study, WRS successfully reduced the BMD via a high bone turnover rate; WRS induced an increase in bone resorption and formation.…”
Section: Discussionmentioning
confidence: 50%
“…VK2 has been shown to exhibit the novel function of binding to the pregnane X receptor (PXR), and PXR-dependent biological functions have been demonstrated in bone (6); however the biological effect of VK2 remains controversial, Effect of vitamin K2 on the development of stress-induced osteopenia in a growing senescence-accelerated mouse prone 6 strain since Fu et al (7) reported that VK2 failed to prevent bone loss in ovariectomized rats. Water-immersion restraint stress (WRS), which involves both psychological and physical stress, is widely used to induce reproducible stress ulcers in experimental animals (8)(9)(10)(11)(12). WRS consists of immobilization and cold stress, in which the exposure temperature is usually 24˚C.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, pre-treatment with Ang-(1-7) signifi cantly reduced the gastric ulcer index, gastric mucosal MDA level with concomitant increase in gastric mucosal concentrations of PGE 2 and NO in comparison with the CRS group. In addition, there was an improvement in the severe gastric damages that were observed by the histological examination.…”
Section: Discussionmentioning
confidence: 73%
“…The Angiotensin (1-7) is an important component of the RAS (2). Ang-(1-7) is a downstream peptide gen erated from angiotensin I through three known enzymes neprilysin (NEP), thimetoligopeptidase (TOP), and prolyloligopeptidase (POP)).…”
Section: Introductionmentioning
confidence: 99%
“…Such a phenomenon has been reported, for example, for amylin [21], adrenomedullin [19], TLQP-21 [16], or recently with angiotensin II [15,45] and substance P [10]. It might be speculated that some neuropeptides, especially in higher doses, are able to cross the brainblood barrier by non-saturable or saturable transport mechanisms using transporters (recently reviewed by Banks [46 ]) and enter the systemic circulation, where they may counteract the centrally induced gastroprotective action via peripheral mechanisms.…”
Section: Gastroprotection Initiated Centrally or Peripherallymentioning
confidence: 93%